Effects of cropping and tree density on earthworm community composition and densities in central Cameroon - Norgrove, L.; Csuzdi, C.; Hauser, S. (Elsevier, 2011)
Earthworms can have positive effects upon crop growth in the tropics. If soils are to be managed sustainably, then more attention should be paid to the effects of cultivation and cropping practices upon earthworms. When forest vegetation is cleared, slashed, burned and land is tilled and cultivated, earthworm abundance, diversity and activity are reduced. Conversely, retaining trees in agroecosystems may maintain earthworm populations during the cropping phase. Here, we assessed the impact on earthworm species diversity and densities of crop cultivation in the understorey of timber plantations thinned to two tree densities and compared these with uncropped, undisturbed timber plantation controls. The plots were reassessed after two and a half years of fallow to see whether populations had recovered. The experiment was in central Cameroon. Seventeen earthworm species were recorded from Eudrilidae subfamilies Eudrilinae and Pareudrilinae, Ocnerodrilidae and Acanthodrilidae, most of which were endemics. This included two new species from two new genera from the sub-family Pareudrilinae, one new species from one new genus of Ocnerodrilidae, two new species of Dichogaster and one new species of Legonodrilus. Ten species were epigeic, six were endogeic and one was anecic. Generally, earthworm densities were lower in cropped plots than in the undisturbed plantation control. The most abundant species was a Legonodrilus sp. nov. with average densities of 49 individuals m−2 in the crop phase and 80 ind. m−2 in the fallow phase. By the fallow phase, densities in the low tree density (120 ind. m−2) were higher than in the high density (40 ind. m−2). The densities of the epigeic Acanthodrilidae were significantly reduced to 7 ind. m−2 in the cropped plots compared with 42 ind. m−2 in the control plots. The effects of cropping were thus species-specific and more work is required to identify which of these endemics are the ecosystem engineers in the system.